Sad by design : on platform nihilism - Lovink, Geert (Digital barricades., 2019)
"Sadness is now a design problem. The highs and lows of melancholy are coded into social media platforms. After all the clicking, browsing, swiping and liking, all we are left with is the flat and empty aftermath of time lost to the app. Sad by Design offers a critical analysis of the growing social media controversies such as fake news, toxic viral memes and online addiction. The failed search for a grand design has resulted in depoliticised internet studies unable to generate either radical critique or a search for alternatives. Geert Lovink calls for us to embrace the engineered intimacy of social media, messenger apps and selfies, because boredom is the first stage of overcoming 'platform nihilism'. Then, after the haze, we can organise to disrupt the data extraction industries at their core."--Back cover of book